Assessment of Population Rate Evolutions in Malaysia and the Republic of China from 1990 Until 2016 - Khairul Amri Kamarudin, Mohd; Abd Wahab, Noorjima; Ekhwan Toriman, Mohd; Razali Abdullah, Mohamad; Safaniza Che Ani, Nurul; Azria, Aisyah; Rahman, Fatin; Azha, Shamira; Nur Aida Zainal, Nik; Kamaruzaman, Fiza (International Journal of Engineering and Technology, 2018)
This study is more focus on identifying the factors that determine the difference of population rates in Malaysia and Republic of China from 1990 to 2016. All the secondary data acquired from the government agencies such as the distribution population, births and deaths in Malaysia and China. The determining factors were classified into two parts, which were the determinants of mortality and determinant of birth rates that at once determine the natural increase factor for the population of the country. Growth of a country will increase when birth rates exceed the death rates. These components are linked to the bases and situations that apply to both countries. The aim objectives are to analyzing the rate of changes of the population and identifying the determinants of population rates. The findings are expected to give a clear picture of the factors that cause the increase and decrease of the population for both countries. Poverty issues, low household income levels, limited employment opportunities and unstable economic conditions are the main reasons why the growth rate of the Malaysian population should be regulated and redesigned. The increasing of population levels that are not balanced with economic improvements will further highlight in the existing issues.Â Â